Identification Of Mold Contaminan In Expired Wet Bread In Tulung Agung - Tri Widodo, Wimbuh (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
Bread is a carbohydrate source that is considered very practical for today's fast-paced and practical life. Mold is one of the microorganisms that cause disease in humans. Mold is the main microorganism that plays an important role in the process of making and spoiling bread. Fungi that are often found in bread spoilage are Rhizopus stolonifer, Penicillium s, and Aspergillus sp. This study used a descriptive research design. The purpose of this study was to determine the presence of mold on wet bread that is no longer suitable for consumption in Tulungagung Regency. The population in this study was bread sold in Tulungagung Regency. The samples of this study were 4 types of bread that are often sold in Tulungagung Regency. pandan brown bread samples contained Aspergillus sp and Rhizopus sp fungal species, banana bread samples contained Aspergillus sp and Rhizopus sp fungal species, steamed bread samples contained Aspergillus sp and Rhizopus sp fungal species, and putu ayu bread samples contained Aspergillus sp and Rhizopus sp fungal species. The conclusion of this research was that the fungal species of Rizhoppus sp and Aspergillus sp were found. This shows that bread that is not suitable for consumption can cause health problems for consumers